Neutron and Photon Dose Rates in a D-T Neutron Generator Facility: MCNP Simulations and Experiments. Issue 6 (June 2020) - Xu, Xu; Yi, Chang; Wanyue, Tang; Yuanming, Sun; Jingbin, Lu; Yumin, Liu; Long, Zhao; Jiaxi, Liu; Xiaoyi, Li
Abstract : Abstract: The deuterium-tritium neutron generator is a common neutron source for fast neutron activation analysis. The 14.1 MeV neutrons emitted from a deuterium-tritium neutron generator are difficult to shield due to their strong penetrability and the induced secondary gamma rays in the shield. A rough calculation based on attenuation factors shows that when 14.1 MeV neutrons with a yield of 1 × 10 8 ns −1 penetrate the designed shielding layers, which consist of a 0.5-m-thick concrete layer and a 0.5-m-thick water layer, the neutron ambient dose equivalent rate is 2.48 μSv h −1 . A geometric model of a neutron shielding room is constructed based on the calculation. Monte Carlo simulations indicate that the highest neutron ambient dose equivalent rate outside the neutron shielding room is 0.73 μSv h −1, and the neutron ambient dose equivalent rate at the detector position in the shielding room is 2.12 μSv h −1 . The experimental results show that the highest neutron ambient dose equivalent rate outside the neutron shielding room is 1.43 μSv h −1, and the neutron ambient dose equivalent rate at the detector position inside the shielding corridor is 2.74 μSv h −1 . Comparative investigations show that the experimental results are basically consistent with the results of the Monte Carlo simulations, except for some positions with large proportions of fast neutrons where it is too difficult for the neutron dose equivalent meter to provide reliable values. Moreover, the radiation dose rate outside the designed shielding room is lower than the occupational exposure dose limit, which is in line with the design expectations. Finally, the gamma spectrum at the position of the gamma detectors is measured by a high-purity germanium detector. The analyzed results show that many secondary gamma rays are generated by the interaction of neutrons with the shield materials and detector probe crystals, and some gamma rays are produced from natural background radionuclides such as 40 K, 208 Tl, 212 Bi, 214 Bi, 212 Pb, 214 Pb, and 228 Ac.